ANALISIS PENGARUH RASIO LIKUIDITAS, LEVERAGE, PROFITABILITAS, AKTIVITAS DAN PASAR TERHADAP RETURN SAHAM (STUDI KASUS: PERUSAHAAN CONSUMER GOODS PERIODE 2012 – 2016) - Boentoro, Nathania Valentine; Widyarti, Endang Tri (Faculty of Economics and Business Diponegoro University, 2018)
Research on the influence of financial ratios has been done. But, there is a gap phenomenon from the data of consumer goods companies where there is fluctuation or instability. The consumer goods companies are fairly stable sector because the product produced in the form of daily necessities products. The purpose of this study is to analyze the influence ratios of liquidity, leverage, profitability, activity and market valuation to stock returns of consumer goods companies in 2012 until 2016.Objects in this study are consumer goods companies listed on the Stock Exchange Indonesia and has a complete annual reports. The research data sourced from Indonesian Market Capital Directory (ICMD) period 2012 until 2016. The selected company is a company that has conducted an Initial Public Offering (IPO) on the research period. The consumer goods companies throughout the research period amounted to 40 companies with to be studied for 30 companies research samples.The result showed that the liquidity ratio measured by current ratio, leverage ratio is measured by debt to equity ratio, profitability ratio is measured by return on equity have a negative but insignificant effect to stock return. While the activity ratio is measured by total asset turnover and market ratio as measures by price to book value have a positif significant effect to stock return.